Steller sea lion (Eumetopias jubatus) consumption of ocean age-0 Chinook salmon (Oncorhynchus tshawytscha) along the northwest coast of Washington State - Zoë K. Lewis; Benjamin W. Nelson; Adrianne M. Akmajian; Jonathan J. Scordino; Elizabeth M. Allyn; Sarah Brown; Dietmar Schwarz; Alejandro Acevedo-Gutiérrez (PLoS ONE, 2025)
The decline of wild Chinook salmon ( Oncorhynchus tshawytscha ) in the Pacific Northwest is concerning due to their critical role in the culture, economy, and ecology of the region, and the endangered species status of some of the evolutionarily significant units. Decline in Chinook stocks has been partially attributed to increases in pinniped abundance. The northwest coast of Washington State, USA, provides year-round habitat to early marine-phase Chinook salmon from multiple stocks and habitat for increasingly abundant Steller sea lions ( Eumetopias jubatus ). We estimated the Chinook salmon biomass consumed by Steller sea lions along the northwest coast of Washington using diet data obtained via DNA metabarcoding from scat and a prey consumption model. Between December 2020 and August 2021, Steller sea lions consumed 284 metric tons (95% PI: 191–417 t) of Chinook salmon. A set of experimental models were used to estimate the consumption of age-0 Chinook salmon, and the base model estimated 146 t (95% PI: 93–221 t) of ocean age-0 Chinook—or approximately 2,064,418 (95% PI: 1,431,524–2,932,922) individual ocean age-0 Chinook— were consumed during the study period. While precise consumption values should be interpreted with caution due to high uncertainty highlighted by sensitivity analyses, our results suggest that Steller sea lions contribute to the low marine survival rates of early marine-phase Chinook salmon at a higher rate than previously estimated. The high uncertainty in model estimates, compounded by assumptions and limitations arising from data gaps, highlights the need for further research on both predator and prey populations in the region.